Pengaruh Kepuasan Konsumen, Harga, Kualitas Produk, Dan Promosi Terhadap Loyalitas Merek Alat Angkat / Crane Xyz Pada Pt.Abc - Tommy Tommy (Universitas Tarumanagara, 2019)
The research aims to determine the effect of customer satisfaction, price, product quality and promotion of brand loyalty of PT ABC lifting equipment (crane). The tool used to obtain the data is a questionnaire using Likert scale. Sampling technique is purposive sampling that is technique of determining sample with certain consideration. The sample in this research is some of PT.ABC consumers in Indonesia which amounted to 50 people, but only 43 respondents who answered this questionnaire. The results show that customer satisfaction has a significant influence on brand loyalty, while price, product quality and promotion have no significant effect on brand loyalty.